2023
DOI: 10.1172/jci.insight.167215
|View full text |Cite
|
Sign up to set email alerts
|

Tregs integrate native and CAR-mediated costimulatory signals for control of allograft rejection

Isaac Rosado-Sánchez,
Manjurul Haque,
Kevin Salim
et al.

Abstract: Tregs expressing chimeric antigen receptors (CAR-Tregs) are a promising tool to promote transplant tolerance. The relationship between CAR structure and Treg function was studied in xenogeneic, immunodeficient mice, revealing advantages of CD28-encoding CARs. However, these models could underrepresent interactions between CAR-Tregs, antigen-presenting cells (APCs), and donor-specific Abs. We generated Tregs expressing HLA-A2–specific CARs with different costimulatory domains and compared their function in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Linked and bystander suppression are thought to be mediated at least in part through Treg-mediated induction of tolerogenic APCs, via removal of co-stimulatory molecules and MHC molecules ( 29 ). To test if NOD A2-CAR Tregs influenced APC activity, the former were co-cultured with HLA-A2 negative or HLA-A2 + NOD splenic dendritic cells (DCs) ( 16 ). After 48 hours, DCs were analyzed for expression of the co-stimulatory molecules CD80 and CD86, and the NOD MHC class II molecule, I-A g7 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Linked and bystander suppression are thought to be mediated at least in part through Treg-mediated induction of tolerogenic APCs, via removal of co-stimulatory molecules and MHC molecules ( 29 ). To test if NOD A2-CAR Tregs influenced APC activity, the former were co-cultured with HLA-A2 negative or HLA-A2 + NOD splenic dendritic cells (DCs) ( 16 ). After 48 hours, DCs were analyzed for expression of the co-stimulatory molecules CD80 and CD86, and the NOD MHC class II molecule, I-A g7 .…”
Section: Resultsmentioning
confidence: 99%
“…Our findings raise the question of where A2-CAR Tregs mediated their effects. Although A2-CAR Tregs suppress DC function ( 16 ), NSG mice have dysfunctional DCs and small, hypocellular lymphoid organs ( 42 ), so in this model, A2-CAR Tregs most likely suppress BDC2.5 T cells at the site of transplantation, resulting in a systemic effect. This possibility is supported by intravital imaging studies of mice with ACE islet transplants and injected with BDC Teff and Tregs which showed that Tregs create long-lasting bonds with BDC2.5 T cells, more so than with DCs, in a partially CTLA-4-dependent manner ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a study conducted by Boroughs and colleagues, using a 4-1BB-based CAR in Tregs had a detrimental impact on their ability to carry out their regulatory functions [99]. Another study by Dawson et al conducted an extensive investigation into how various co-stimulatory domains influence the function of an anti-HLA-A2 CAR in an allotransplantation model [100,101]. Their data revealed that the CAR encoding CD28 was more effective both in vitro and in vivo concerning proliferation, suppression, and the delay of GvHD symptoms, while the presence of 4-1BB-CAR had a negative impact on Treg function and stability [100].…”
Section: Tregs Selectionmentioning
confidence: 99%